Genetic Transformation of Orchid Dendrobium Sonia-17 Using the Biolistic Method - Abdullah, Janna Ong (2001)
The ever-changing tastes and preferences of orchid consumers initiated the need to create new and better varieties. Progress in molecular biology has allowed genetically well defined characteristics to be added to the gene pools, thereby increasing the potential for genetic improvement. However, such effort at creating a custom-made flower has yet to be realised in orchids. The present study aims at developing a genetic transformation system for the introduction of specific foreign genes into orchid. Protocorm-like-bodies (PLBs) of orchid hybrid, Dendrobium Sonia-17, were established to be suitable target tissues for the introduction of foreign genes using the biolistic method. They were easily micropropagated in vitro that provided plenty of materials to work with and were a reliable source of potentially regenerabIe tissues. The effect of blasting on the growth of the PLBs was evaluated by subjecting the PLBs to bombardment with uncoated gold microparticles. One month following bombardment, fresh weights gained by the PLBs were recorded. The results showed that bombarded PLBs had higher weight increments compared to non-bombarded treatments, indicating that subsequent lethal responses by the PLBs on antibiotic selections were mainly due to the selection pressure and not as a result of injuries inflicted during the bombardment.